KONSTRUKSI"ERGATIF BARU" DALAM BAHASA NUSANTARA - Arifin, Zaenal (Kajian Linguistik dan Sastra, 2006)
Part of human language in the world has characteristics of accusative syntax, which treats intransitive subject (S) and transitive subject (A) in the same way (unmodified), whereas transitive object (O) is treatd differently (modified). Another part of human language has ergative arrangement, which trears intransitive subject (S) and transitive object (O) in the same way (unmodified), whereas transitive subject (A) is treated differently (modified). In linguistic study in the Indonesian Archipelago, active and passive voice are widely known. Passive voice can be changed into active one and conversely, active voice (transitive) can be changed into passive one. The Indonesian and Sundanese language have also passive voice that is antiactive (cannot be changed into active) and active voice that is antipassive (cannot be changed into passive). These forms are suspected to be "new ergative" form.Â Key words:Â accusative, ergative, active, passive, antiactive, antipassive, modified, and unmodified